Beta vulgaris Extract as a Post-Cholecystectomy Dietary Intervention: A Systematic Review of its Effects on Gut Microbial Balance, Bile Acid Metabolism, and E. Coli/Lactobacillus Dynamics - Benedick Johanes Alvian; Sigit Adi Prasetyo; Yora Nintida (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Cholecystectomy, while a common surgical procedure, significantly alters bile acid dynamics and the gut microbiome, potentially leading to an imbalance favoring opportunistic pathogens like Escherichia coli over beneficial bacteria like Lactobacillus. This systematic review investigates the potential of beetroot (Beta vulgaris) extract, rich in betalains and prebiotic fibers, as a dietary intervention to mitigate these post-cholecystectomy microbial shifts. Methods: A systematic search of PubMed, Scopus, Web of Science, and Cochrane Library databases was conducted for studies published between 2013 and 2024. Keywords included "cholecystectomy," "gallbladder removal," "bile acids," "Escherichia coli," "Lactobacillus," "beetroot," "Beta vulgaris," "prebiotic," "gut microbiome," and related terms. Studies investigating the effects of Beta vulgaris (or its constituents) on gut microbial composition, bile acid metabolism, or relevant clinical outcomes in post-cholecystectomy contexts (human or animal models) were included. Quality assessment was performed using the Cochrane Risk of Bias 2.0 tool for randomized controlled trials (RCTs) and the ROBINS-I tool for non-randomized studies. Results: Seven studies met the inclusion criteria: three human RCTs, two animal studies (rats), and two in vitro studies. The human studies were of moderate to high risk of bias. The animal studies had a lower risk of bias but limited direct applicability to humans. The in vitro studies provided mechanistic insights but lacked the complexity of the in vivo environment. Due to the heterogeneity of study designs and outcome measures, a meta-analysis was not feasible. Beetroot extract supplementation (standardized to betalain content) was associated with a significant increase in Lactobacillus abundance (mean increase of 15%, p < 0.05) and a decrease in E. coli abundance (mean decrease of 10%, p < 0.05) in the post-cholecystectomy gut. There was also a shift in bile acid profiles, with an increase in secondary bile acids known to be less inhibitory to Lactobacillus. Conclusion: While existing evidence is limited, the theoretical basis and preliminary findings suggest that beetroot extract holds promise as a post-cholecystectomy dietary intervention to promote a healthier gut microbiome. Further high-quality, well-powered RCTs are warranted to confirm these potential benefits and elucidate the underlying mechanisms.